Large Fibroepithelial Polyp of Vulva. (24th November 2011) - Navada, Mahesha H.; Bhat, Poornima Ramachandra B.; Rao, Sujaya V.; G., Nagarathna
Abstract : A rare case of a large fibroepithelial polyp (FEP) of the vulva is described. The polypoidal growth was 10 cm in its largest diameter, having a long pedicle with features of inflammation secondary to infection, and was found arising from the left labia majora. The patient did not manifest any signs of recurrence following excision. A large and infected FEP of the vulva is a rare occurrence and hence reported.